The cooling history of the late Pliocene Eldzhurtinskiy granite (Caucasus, Russia) and the thermochronological potential of grain-size/age relationships - Hess, Jürgen C.; Lippolt, Hans J.; Gurbanov, A. G.; Michalski, I. (Earth and planetary science letters, 1993)
Isotopic age investigations have been carried out on samples from the late Pliocene Eldzhurtinskiy granite (Great Caucasus, Russia) in order to elucidate the cooling history of this kilometere sized plutonic body. The samples were taken from a horizontal profile (from the edge to the centre of the granite) and from a vertical profile (from the top to a depth of 4570 m). The 40Ar/39Ar results on biotites ranging from 2.5 to 1.2 Ma indicate a vertical age zoning of the granite caused by regional uplift. An uplift rate of 4 mm/a is calculated from the age differences. Together with the results of fission track dating on apatite and zircon and the present-day rock temperatures the biotite ages can be used to evaluate cooling rates below 400°C. The cooling rates of about 180°C/Ma are relatively high and spatially and temporarily fairly uniform throughout the granite. A geothermal gradient of 45°C/km is derived from uplift and cooling rates; this is identical to the present-day borehole gradient. The 40Ar/39Ar ages of distinct biotite grain fractions from one and the same sample specimen are discordant. Generally, they show clear age/grain-size correlation, as expected from Ar diffusion theory for cooling systems. Thus, the biotite results support the additional detailed thermochronological information. The cooling rates in the temperature range of biotite closure, based on the grain-size/age correlations of the biotites, are close to 180°C/Ma. They provide evidence that within a certain temperature interval the time-temperature path of a rock may be determined exclusively by isotopic dating of different grain-size fractions of only one type of mineral.
Elektronische Reproduktion der Druck-Ausgabe 9. Oktober 2002
Gesehen am 27.02.2023